Empirical evidence of the relationship between financial development and economic growth : the case of China. - Chen, Wanyi. (2009)
The objective of this paper is to empirically examine the relationship between financial development and economic growth in the context of China during the post-1978 reform period. We employ China's provincial data from 1985 to 2004 and apply the recent Generalized Method of Moments technique developed for dynamic panels. Our financial development indicators are the ratio of total bank loans to GDP, the ratio of household deposits to GDP, and the ratio of total market capitalization at the time of IPO of all companies incorporated in the province to GDP. The first two are banking development indicators while the last variable is the indicator for stock market development. We also use a set of controll variables to control for other economic phenomena.